Medicinal and antioxidant activity of Garcinia pedunculata: a valuable underutilized fruit of Assam - Islam, Jasmin; Devi , Ph Vivekanandini Ph Vivekanandini; Langching , Jyoti (Journal of Postharvest Technology, 2021)
Garcinia pedunculata commonly known as “Amlavetasa” in India, and “Taikor” in Bangladesh, is an evergreen tree with a fluted trunk and short  spreading branches. The fruit is globose with a diameter of 8-12 cm and has fleshy edible aril. The ripe fruit is golden yellow in colour. The  mature fruit is usually eaten raw or cooked with pulses or with other vegetables. It is available particularly in Assam, Arunachal Pradesh and  West Bengal regions of India. Usually, the ripe or raw fruits are sliced, sun-dried and preserved. The raw fruits are preferred for pickles and  sundried fruits are used as spices in foods. Traditionally, the plant has been used for many ailments such as chronic catarrh, asthma, cough,  bronchitis, fever, dysentery and as a cardiotonic. Since Garcinia species has a lot of medicinal properties and is considered as an underutilized  fruit, so a review work was carried out to study its medicinal and antioxidant properties and products developed using Garcinia, with special  reference to Garcinia pedunculata.
Keywords: Garcinia pedunculata; antioxidant activity; medicinal properties; underutilized; value addition